Increasing project success in wellhead and christmas tree manufacturing equipment through risk management culture - Hamid, Abdul; Baba, Ishak; Tamin, Norfauzi; Darmawan, Agong Setyo; Sani, Winardi (2023)
The primary equipment for oil production, manufactured in a plant, is the wellhead and Christmas tree. By creating a standardized set of risk instruments and a risk management framework, embedding risk management into organizational culture will reduce the overhead of imposing risk management on every new manufacturing project. This study's goal is to improve project success by examining the culture of risk management practices in the production of wellhead and Christmas tree equipment. The information was gathered from companies in Malaysia and Batam, Indonesia, with 161 respondents in a population study. Employing Cronbach's alpha to analyze the descriptive data and determine its significance. The Cronbach alpha and significant value are displayed consequently. The study's data came from a post-survey and survey using a Google link form of companies with stock listed in Malaysia and Batam, Indonesia. These results show that risk culture and staff competency may be created as important variables to improve risk management implementation in manufacturing, based on descriptive statistical analysis. This paper shows how to create a multicultural project management process and raise project success rates by adhering to this approach